GUIDED IMAGERY: KONSEP KONSELING KREATIF UNTUK PENANGGANAN POST TRAUMATIC STRESS DISORDER (PTSD) - Yulianto, author (JURNAL FOKUS KONSELING, 2015)
Everyone has a different reaction in facing the extraordinary events that are triggered by the teribble events. They clash psychic cause post traumatic stress disorder or in Post Traumatic Stress Disorder (PTSD). To solve it can be done through treatment with pharmacotherapy and psychotherapy. In psychotherapy handling, one of the techniques that can be used is the technique of guided imagery as one of the PTSD treatment efforts. This technique is an effort that can be used to deal with a difficult client to communicate verbally. Communication is the basis of the counseling relationship. Implementation of counseling through guided imagery techniques are considered able to help clients resolve clientâs problems. In this technique, clients are guided to be able to focus on positive thoughts and imaginations that lead to negative events experienced to be able to create a positive picture of the imagination.Keywords: Guided imagery, post traumatic stress disorder (PTSD), Creative counseling